Bogota 1988-2008: Change-driven intentions granting power for action (REVISTA NODO, 2010)
The article depicts the how and the why empirical urban reality is a product of a normative text, the foremost statement of the research project Textual Bogota. To attest it, a series of documents and texts produced by all eight mayoral terms between 1988 and 2008 were analyzed, evaluated and contrasted, among which the City Development Plan proposed by each administration and the Territorial Planning Strategy were mostly considered. The authoress emphasizes on the importance given to words and norms themselves on theresearch, and then analyzes three conceptual categories that support the study: utopian model, device and performative utterance. It concludes that during the time period of examination the mayoralty gathered enough power to impose new ways of conceiving public management, regional planning, territorial strategies and future policies, and that that power is called performativity.
Keywords: Urban utopia; performative utterance; public policy; normative; power; language; Bogota